2012
DOI: 10.1088/0964-1726/22/1/014014
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive wettability-enhanced surfaces ordered on molded etched substrates using shrink film

Abstract: Superhydrophobic surfaces in nature exhibit desirable properties including self-cleaning, bacterial resistance, and flight efficiency. However, creating such intricate multi-scale features with conventional fabrication approaches is difficult, expensive, and not scalable. By patterning photoresist on pre-stressed shrink-wrap film, which contracts by 95% in surface area when heated, such features over large areas can be obtained easily. Photoresist serves as a dry etch mask to create complex and high-aspect rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 36 publications
(43 reference statements)
0
14
0
Order By: Relevance
“…The photoresist layer was removed using acetone. Patterned Au and PO films were then lifted from their Si wafer supports and heated past the PO glass transition temperature (125 uC) using a commercial heat gun (Steinel HL1820S), shrinking the patterned electrodes by 95% within seconds 20,27 ( Fig. 2A-C).…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…The photoresist layer was removed using acetone. Patterned Au and PO films were then lifted from their Si wafer supports and heated past the PO glass transition temperature (125 uC) using a commercial heat gun (Steinel HL1820S), shrinking the patterned electrodes by 95% within seconds 20,27 ( Fig. 2A-C).…”
Section: +mentioning
confidence: 99%
“…It has been previously shown that heterogeneous, rough structures create anti-wetting behavior. 20,30 Additionally, creating large contrast between surface energies on a single substrate allows precise spatial control of small liquid volumes. 20 The contrast between patterned Au thin films and exposed PO areas allows for the same effect.…”
Section: Electrode Characterization and Performancementioning
confidence: 99%
“…The metal-deposited SMP was then heated past its glass transition temperature (100 °C) in a convection oven set to 140 °C for 13 min, causing it to shrink roughly 67% in area [ 23 ]. The stiffness mismatch between the metallic thin film and the substrate causes the film to buckle and form hierarchical wrinkled structures [ 24 ]. The sample is then immersed in a 5 mM (3-mercaptopropyl) trimethoxysilane (95% MPTMS) ethanol solution for 1 h at room temperature to functionalize the Au surface.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, such wrinkle structures have been extensively characterized and leveraged for various applications [4042, 44, 4754]. Recent work has even shown that the wrinkles can be somewhat deterministic [47].…”
Section: Fabrication and Characterization Of Composite Structuresmentioning
confidence: 99%
“…When the shrink film retracts, the thin stiffer metal films buckle to create ‘wrinkle’ structures [4044]. This film shrinks considerably more than previously reported and thus results in significantly smaller structures [4547].…”
Section: Introductionmentioning
confidence: 99%